Community Leaders Confronting Inequalities in a Highly Vulnerable Territory in Cubatão, São Paulo: Perceptions and Articulations - Hailton Yagiu; Carlos Roberto Castro-Silva (Avances en Psicología Latinoamericana)
This article aims to investigate how community leaders think, feel, live, and act in the struggle for better living conditions in a highly vulnerable territory, while reflecting on the articulations that occur within it. The research employed a qualitative documentary method based on a pre-existing database. The information was processed and systematized using Atlas.ti software and analyzed using Thompson’s Depth Hermeneutics, along with González-Rey’s Qualitative Epistemology. The results showed that, upon arriving in the territory, the primary concerns were the lack of infrastructure and basic sanitation. Today, the main challenges are issues related to drug trafficking and the future of adolescents. It is concluded that community leaders contribute to the reorganization of the community in response to challenges and difficulties. They serve as a hub for initiatives, demonstrating a strong capacity for articulation and mobilization to foster community development and empowerment.